2010
DOI: 10.1024/0300-9831/a000005
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-oryzanol Ameliorates Insulin Resistance and Hyperlipidemia in Rats with Streptozotocin/nicotinamide-induced Type 2 Diabetes

Abstract: Gamma-oryzanol is a component of rice bran oil (RBO) with purported health benefits. This study evaluated the effects of gamma-oryzanol on insulin resistance and lipid metabolism in Wistar rats with type 2 diabetes (T2DM). The rats were divided into three groups and consumed one of the following diets for 5 weeks: 15 % soybean oil (control group); 15 % palm oil (PO); and 15 % PO with the addition of 5.25 g gamma-oryzanol (POO). The results showed that PO markedly increased plasma low-density-lipoprotein choles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 0 publications
1
28
0
Order By: Relevance
“…This model is seen as increasingly important because, in contrast to genetically generated mouse strains that dominate the experimental literature, it closely resembles the most common human condition, termed sporadic AD. There is now a considerable literature on the use of SZT to establish models of insulin resistance (Blondel and Portha, 1989;Koopmans et al, 2006;Cheng et al, 2010;Thackeray et al, 2011). As reviewed previously (de la Monte and Wands, 2008), these SZT-induced changes could be reduced or prevented by early treatment with peroxisome proliferatoractivated receptor agonists in doses smaller than routinely used to treat diabetes type 2.…”
Section: A Streptozotocin Model For Diabetes and Alzheimer's Diseasementioning
confidence: 99%
“…This model is seen as increasingly important because, in contrast to genetically generated mouse strains that dominate the experimental literature, it closely resembles the most common human condition, termed sporadic AD. There is now a considerable literature on the use of SZT to establish models of insulin resistance (Blondel and Portha, 1989;Koopmans et al, 2006;Cheng et al, 2010;Thackeray et al, 2011). As reviewed previously (de la Monte and Wands, 2008), these SZT-induced changes could be reduced or prevented by early treatment with peroxisome proliferatoractivated receptor agonists in doses smaller than routinely used to treat diabetes type 2.…”
Section: A Streptozotocin Model For Diabetes and Alzheimer's Diseasementioning
confidence: 99%
“…It had previously shown that the STZ-induced diabetic rats treated with tocotrienol-rich fraction from palm oil could potentially stabilize the level of total cholesterol, LDLcholesterol, and triglycerides 31 . In addition, cholesterol synthesis and fuel oxidation were increased in STZ/nicotinamide-induced diabetic rats treated with γ-tocotrienol and γ-oryzanol rich fractions of rice bran oil as a result of hyperlipidaemic and hyperinsulinemic response suppression 32 . HMGCoA reductase, the key enzyme in cholesterol synthesis, was primarily targeted by tocotrienols.…”
Section: Discussionmentioning
confidence: 99%
“…The compound has been shown to improve insulin resistance and hyperlipidemia in Wistar rats with streptozotocin/nicotinamide-induced type 2 diabetes (Cheng, Ma et al 2010). In addition, it has stimulated the secretion of adiponectin, a hormone of the adipose tissue whose deficiency is linked to the insurgence of insulin resistance (Nagasaka, Yamsaki et al 2011;Ohara, Kiyotani et al 2011).…”
Section: Diabetes and Metabolic Syndromementioning
confidence: 98%